Drug absorption efficiency in Caenorhbditis elegans delivered by different methods. - Shan-Qing Zheng; Ai-Jun Ding; Guo-Ping Li; Gui-Sheng Wu; Huai-Rong Luo (PLoS ONE, 2013)
BACKGROUND: Caenorhbditis elegans has being vigorously used as a model organism in many research fields and often accompanied by administrating with various drugs. The methods of delivering drugs to worms are varied from one study to another, which make difficult in comparing results between studies. METHODOLOGY/PRINCIPAL FINDINGS: We evaluated the drug absorption efficiency in C. elegans using five frequently used methods with resveratrol with low aqueous solubility and water-soluble 5-Fluoro-2'-deoxyuridine (FUDR) as positive compounds. The drugs were either applied to the LB medium with bacteria OP50, before spreading onto Nematode Growth Medium (NGM) plates (LB medium method), or to the NGM with live (NGM live method) or dead bacteria (NGM dead method), or spotting the drug solution to the surface of plates directly (spot dead method), or growing the worms in liquid medium (liquid growing method). The concentration of resveratrol and FUDR increased gradually within C. elegans and reached the highest during 12 hours to one day and then decreased slowly. At the same time point, the higher the drug concentration, the higher the metabolism rate. The drug concentrations in worms fed with dead bacteria were higher than with live bacteria at the same time point. Consistently, the drug concentration in medium with live bacteria decreased much faster than in medium with dead bacteria, reach to about half of the original concentration within 12 hours. CONCLUSION: Resveratrol with low aqueous solubility and water-soluble FUDR have the same absorption and metabolism pattern. The drug metabolism rate in worms was both dosage and time dependent. NGM dead method and liquid growing method achieved the best absorption efficiency in worms. The drug concentration within worms was comparable with that in mice, providing a bridge for dose translation from worms to mammals.